: [под редакцией С. А. Мохначёва] - Мохначев Сергей Анатольевич (2002)
Экземпляры: КР (20030127) / Инвентарный номер: у55080 / Цена: 30.00 / Сис.шифр: 65.29 / Авт.знак: М 86 / ГРНТИ: 06.56.21 / ББК: 65.263